2020
DOI: 10.1111/jvp.12871
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy and pharmacodynamic profiles of four polyether ionophores against methicillin‐resistant Staphylococcus spp.

Abstract: The objective of this study was to determine the minimum inhibitory concentrations (MICs) and pharmacodynamic profiles of four ionophores (lasalocid, monensin, narasin and salinomycin) against staphylococcal isolates from clinical cases of human and veterinary staphylococcal infections, and to determine the effect of methicillin resistance on the antimicrobial activity of ionophores. Broth microdilution MIC testing was used to determine antimicrobial activity against 156 staphylococcal isolates of human and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A study carried out in 2010 showed that using in-vitro experiments, low concentrations of salinomycin, narasin, monensin, and lasalocid had an antibacterial activity for Gram-positive bacteria such as Streptococcus uberis in ruminants [ 97 ]. A recent study determined that polyether ionophores could also be used against methicillin-resistant staphylococci [ 98 ]. Stefańska et al showed that in vitro salinomycin significantly affected methicillin-resistant Staphylococcus epidermis , including 70% inhibition of biofilm formation [ 99 ].…”
Section: Other Clinical Uses Of the Ionophoresmentioning
confidence: 99%
“…A study carried out in 2010 showed that using in-vitro experiments, low concentrations of salinomycin, narasin, monensin, and lasalocid had an antibacterial activity for Gram-positive bacteria such as Streptococcus uberis in ruminants [ 97 ]. A recent study determined that polyether ionophores could also be used against methicillin-resistant staphylococci [ 98 ]. Stefańska et al showed that in vitro salinomycin significantly affected methicillin-resistant Staphylococcus epidermis , including 70% inhibition of biofilm formation [ 99 ].…”
Section: Other Clinical Uses Of the Ionophoresmentioning
confidence: 99%